Legal Personality as a Theoretical Approach to Non- State Entities in International Law: The Example of Transnational Corporations - Muhvić, Davor (Pécs journal of international and European law, 2017)
In the last decades we are witnessing the intensive strengthening of normative ties of a series of non- state entities (e.g. transnational corporations, international non-governmental organizations and international terrorist groups) with international law. Due to the traditional state-centrism of the doctrine of international legal personality in contemporary international law, there is a tendency of using in this context such terms as participants in international law, users of international law, non- state actors in international law or terms focusing on specific international legal rights and obligations of a particular entity. Notwithstanding certain valuable contributions of these theoretical approaches, the author nevertheless advocates the theoretical consideration of this matter within the traditional institution of (international) legal personality. The paper gives an overview of existing and emerging international legal rights and obligations of transnational corporations as an example of prominent non-state entities in international law. On the basis of this overview the author analyzes some of the basic theoretical issues related to international legal personality – the issue of the necessary nature and scope of legal capacity and that of the use of the term "direct" in defining a subject of international law.